Comparison of methods for static charge energy harvesting on aircraft - Kiziroglou,ME; Becker,T; Yeatman,EM; Schmid,U; Evans,JW; Wright,PK (Society of Photo-optical Instrumentation Engineers (SPIE), 2017)
In this paper, the possibility of using the static charge that accumulates on aircraft during flight as a source to power monitoring sensors is examined. The assessed methods include using a pair of materials with different air-flow charging rates, contact discharging of the fuselage to neutral metallic bodies, charge motion induction by the fuselage field and inductive harvesting of fuselage-to-air corona discharges at static discharge wicks. The installation and potential advantages of each method are discussed. The feasibility of directly charging a storage capacitor from accumulated static charge is studied experimentally, demonstrating a voltage of 25V on a 25nF capacitor.